Neuroprotective effects of the new Na channel blocker rs100642 in global ischemic brain injury - ÖZTANIR, MUSTAFA NAMIK; KAMIŞLI, SUAT; Basaran, Cenk; BATÇIOĞLU, KADİR; ÖZTANIR, MUSTAFA NAMIK; GÜL, MEHMET; SATILMIŞ, BASRİ; UYUMLU, AYŞE BURÇİN; KAYHAN, BAŞAK; Genc, Metin (My University, 2019)
Introduction: RS100642, a mexiletine analogue, is a novel sodium channel blocker with neuroprotective and antioxidant activities. The protectivity of RS100642, which has been shown against focal cerebral ischemia, was investigated in global cerebral ischemia in this study.